2008
DOI: 10.1016/j.ijpharm.2008.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Peptide prodrugs: Improved oral absorption of lopinavir, a HIV protease inhibitor

Abstract: Lopinavir (LVR) is extensively metabolized by CYP3A4 and is prevented from entering the cells by membrane efflux pumps such as P-gp and MRP2. In an approach to evade the first-pass metabolism and efflux of LVR, peptide prodrugs of LVR [valine-valine-lopinavir (VVL) and glycine-valinelopinavir (GVL)] were synthesized. Prodrugs were identified with 1 H and 13 C NMR spectra and LC/ MS/MS was employed to evaluate their mass and purity. Solubility studies indicated that the prodrugs have much greater solubility as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 14 publications
3
52
0
Order By: Relevance
“…Significant improvement in aqueous solubility by amino acid and dipeptide prodrugs may generate compounds amenable for topical administration. Results obtained from prodrug aqueous solubility are consistent with previously published reports from our laboratory (36)(37)(38).…”
Section: Aqueous Solubility Studiessupporting
confidence: 91%
“…Significant improvement in aqueous solubility by amino acid and dipeptide prodrugs may generate compounds amenable for topical administration. Results obtained from prodrug aqueous solubility are consistent with previously published reports from our laboratory (36)(37)(38).…”
Section: Aqueous Solubility Studiessupporting
confidence: 91%
“…The culture medium was replaced every alternate day during the growth period. 16 Prodrugs stability in rPCEC and rabbit ocular tissue homogenates Hydrolysis of prodrugs was performed in cell and ocular tissue homogenates. The method is described in the following sections.…”
Section: Cell Culturementioning
confidence: 99%
“…The quantity of formazan product was measured at 485 nm, and the absorbance is directly proportional to the number of living cells in the culture. 16,17 Uptake studies Uptake studies were conducted with confluent rPCECs. Cells were washed thrice with DPBS after aspirating the medium from each well.…”
Section: Cytotoxicity Studiesmentioning
confidence: 99%
“…Our laboratory has reported that dipeptide prodrug derivatization of effl ux pump substrates such as quinidine, saquinavir, and lopinavir causes significant reduction in their affi nity toward effl ux pumps. [35][36][37] This hypothesis holds true even in this study, where affi nity toward effl ux pumps is slightly diminished due to prodrug modifi cation. But, it is important to note that complete evasion of effl ux could be realized by simultaneously targeting an infl ux nutrient transporter.…”
Section: Cellular Accumulation Of Bimatoprost In Rpcec In the Presencmentioning
confidence: 51%
“…But, it is important to note that complete evasion of effl ux could be realized by simultaneously targeting an infl ux nutrient transporter. [35][36][37] Finally, the extent of effl ux inhibition in the presence of specifi c inhibitors in rPCEC might be comparatively less, since it is a primary culture in comparison to MDCK-transfected cell lines employed in this study, which overexpresses effl ux proteins.…”
Section: Cellular Accumulation Of Bimatoprost In Rpcec In the Presencmentioning
confidence: 99%